Religious Moderation (Role revitalization of the Mosque in Developing Moderate Islamic Understanding in The Muslim community of Bengkulu) - Jafar, Wahyu Abdul; Mursalin, Supardi; Fathimah, Iim; Jaya, Dwi Putra (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted to describe social facts related to the role of mosques in developing moderate Islamic understanding. During Rosulluloh, the mosque was the center of activities that dealt with all problems of community life, whereas now the mosque is only dealt with matters of ubudiyah (matters of worship).There are several important issues examined in this study, namely the role of the mosque and obstacles encountered in developing moderate Islamic understanding in the city of Bengkulu. This is field research. the approach used in this research is the sociological approach. In this study, researchers used two techniques in collecting data, namely: Interviews and documentation. After conducting the research, several important conclusions were found, among others: The role of the mosque that has been don in developing Moderate Islamic Understanding is filtering lecture material. While the obstacles encountered are group fanaticism, primordialism (excessive tribal feelings), lack of religious knowledge, nepotism and the desire to get money/ wealth from the mosque.